Facile synthesis, formation mechanism and tunable upconversion luminescence of nanocrystals co-doped by Yb3+/Tm3+. (March 2017) - Jiao, Jiqing; Yang, Huasen; Fang, Chenchen; Tang, Jianguo; Wang, Yao; Huang, Linjun; Liu, Jixian; Wang, Wei; Gai, Shasha; Li, Yao; Kipper, Matt J.; Belfiore, Laurence A.
Graphical abstract: The work provided not only a simple method to prepare UCNPs but also the mechanism for tunable upconversion luminescence. Highlights: UCNPs (GdF3, YF3, NaGdF4 and NaYF4 ) co-doped by Yb 3+ /Tm 3+ had been synthesized at 150 °C. The growth process and upconversion mechanism of UCNPs had been deduced by schematic diagram. The accumulation and energy transfer of Gd 3+ could be demonstrated in the polycrystalline host. Abstract: The well-defined lanthanide co-doped upconversion nanoparticles(UCNPs) had been synthesized using a simple solvothermal route at 150 °C, which was lower than previous reports. The shuttle-like and spherical UCNPs co-doped by Yb 3+ /Tm 3+ had been prepared, respectively. The morphology, crystal phase and size distribution of various UCNPs could be easily controlled. The growth mechanism and morphology transition of UCNPs had been deduced by schematic diagram. UC luminescence could be tuned by employing different host lattices (GdF3, YF3, NaGdF4 and NaYF4 ). NaGdF4 :Yb 3+ /Tm 3+ displayed the strongest UC luminescence at 475 nm among four kinds of UCNPs, and its emission intensity was almost 10 times higher than that of NaYF4 :Yb 3+ /Tm 3+ . UC mechanism had been determined by energy level diagrams. It's revealed that the accumulation and energy transfer of Gd 3+ could be demonstrated in polycrystalline structure. The work provided a simple method for preparation of UCNPs with tunable UC luminescence.